War in the Middle Ages - Contamine, Philippe; Jones, Michael (Oxford Blackwell, 1984)
Covering the ten centuries following the fall of Rome, War in the Middle Ages engages all aspects of its subject, including the military customs and conditions of the various Western European states; armor and weaponry recruitment; and rules of combat developed to limit bloodshed.Philippe Contamine writes with an awareness that, in both theory and fact, medieval warfare was constantly evolving. He opens with a chapter on Roman military disintegration and the practice of warfare in the barbarian kingdoms erected on the empire's ruins. He then shows how feudalization multiplied conflicts, and describes the resulting growth of the "great stone civilization" of the castle. In the area of military method, he emphasizes three innovations: gunpowder, standing armies and the increased use of infantry, supplying in each case a wealth of data and documentation.Contamine traces the rise of a new literature of strategy and changes in the concept of courage which he puts in the context of actual risk. He points out that the chivalric ideals of the later Middle Ages operated within narrow limits, outside which aristocrats and commoners freely slaughtered each other. Contamine also analyzes the theories of just and unjust war that developed at this time, and illustrates a phenomenon more typical of the period; the religious glorification of the warrior.Ever mindful of the chaos and devastation that war brings, War in the Middle Ages nonetheless offers a clear and consistent picture of the military ethos of a millennium.
Keywords: Middle Ages (500-1400); War; Military history